Recent progress in diagnosis and treatment of Human African Trypanosomiasis has made the elimination of this disease a realistic target by 2030 - Álvarez-Rodríguez, Andrés; Jin, Bo-Kyung; Radwanska, Magdalena; Magez, Stefan (Frontiers in Medicine, 2022)
Human African Trypanosomiasis (HAT) is caused by unicellular flagellated protozoan parasites of the genus Trypanosoma brucei. The subspecies T. b. gambiense is mainly responsible for mostly chronic anthroponotic infections in West- and Central Africa, accounting for roughly 95% of all HAT cases. T. b. rhodesiense results in more acute zoonotic infections in East-Africa. Because HAT has a two-stage pathogenesis, treatment depends on clinical assessment of patients and the determination whether or not parasites have crossed the blood brain barrier. Today, ultimate confirmation of parasitemia is still done by microscopy analysis. However, introduction of diagnostic lateral flow devices has been a major contributor to the recent dramatic drop in T. b. gambiense HAT. Other techniques such as Loop Mediated Isothermal Amplification (LAMP) and Recombinant Polymerase Amplification (RPA)-based tests have been published but are still not widely used in the field. Most recently, CRISPR-Cas technology has been proposed to improve the intrinsic diagnostic characteristics of molecular approaches. This will become crucial in the near future, as preventing the resurgence of HAT will be a priority and will require tools with extreme high positive and negative predicted values, as well as excellent sensitivity and specificity. As for treatment, pentamidine and suramin have historically been the drugs of choice for the treatment of blood-stage gambiense/rhodesiense-HAT respectively. For treatment of second-stage infections, drugs that pass the blood brain barrier are needed, and melarsoprol has been effectively used for both forms of HAT in the past. However, due to the high occurrence of post-treatment encephalopathy, the drug is not recommended for use in T. b. gambiense HAT. Here, a combination therapy of eflornithine and nifurtimox (NECT) has been the choice of treatment since 2009. As this treatment requires IV perfusion of eflornithine, efforts were launched in 2003 by the Drugs for Neglected Disease Initiative (DNDi) to find an oral-only therapy solution, suitable for rural sub-Saharan Africa treatment conditions. In 2019 this resulted in the introduction of fexinidazole, with a treatment regimen suitable for both the blood-stage and non-severe second-stage T. b. gambiense infections. Experimental treatment of T. b. rhodesiense HAT has now been initiated as well.